2012
DOI: 10.1007/s10393-012-0781-7
|View full text |Cite
|
Sign up to set email alerts
|

Retinol Assessment Among Women and Children in Sahelian Mobile Pastoralists

Abstract: Micronutrient deficiencies are widespread in developing countries, particularly in remote communities such as mobile pastoralists. The nutritional and vitamin A status of this population is not well-documented in Chad. This study assessed serum retinol levels among women and children under five-year-old in nomadic and semi-nomadic pastoralist and rural-settled communities, who are similarly exposed to risk factors such as gastrointestinal parasitic infection, anaemia and emaciation. The novel method of portabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 19 publications
0
11
0
4
Order By: Relevance
“…Milk and milk products are the main animal sources for vitamin A (Codjia, ) and frequently consumed by pastoralist communities particularly during the rainy season (Galvin, ). In children from nomadic Chadian pastoralists, serum retinol concentrations were higher than in children from settled pastoralists consuming less milk and milk products (Bechir et al, ). Goat and cow milk were reported to be important sources of vitamin A in Chadian pastoralist, and the retinol concentrations of milk significantly correlated with the human serum retinol concentration (Zinsstag et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Milk and milk products are the main animal sources for vitamin A (Codjia, ) and frequently consumed by pastoralist communities particularly during the rainy season (Galvin, ). In children from nomadic Chadian pastoralists, serum retinol concentrations were higher than in children from settled pastoralists consuming less milk and milk products (Bechir et al, ). Goat and cow milk were reported to be important sources of vitamin A in Chadian pastoralist, and the retinol concentrations of milk significantly correlated with the human serum retinol concentration (Zinsstag et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…; Bechir et al . , ; Münch ). There is a direct relation between the levels of vitamin A in women's blood and levels in the milk of their livestock.…”
Section: Results Of the Researchmentioning
confidence: 99%
“…Many women and children suffered from malnutrition during dry years (Bechir 2010;Bechir et al 2010;M€ unch 2012), whereas malnutrition is rarely reported in years with much rain (Daugla et al 2004;Zinsstag et al 2010). Fresh fruit and vegetables are not consumed, so that milk is the only source of vitamin A, which can lead to deficiency symptoms (Zinsstag et al 2002;Bechir et al 2011Bechir et al , 2012bM€ unch 2012). There is a direct relation between the levels of vitamin A in women's blood and levels in the milk of their livestock.…”
Section: Human and Animal Healthmentioning
confidence: 99%
“…; Bechir et al . , 2012b; Münch ). Un lien direct a pu être établi entre le taux de vitamine A dans le sang des femmes et du lait de leur bétail.…”
Section: Résultats De Rechercheunclassified
“…Des etudes ont montr e que beaucoup de femmes et d'enfants souffrent de malnutrition durant les ann ees de s echeresse (Bechir 2010;Bechir et al 2010;M€ unch 2012), au contraire, la sous-alimentation est rarement constat ee au cours des ann ees riches en pluie (Daugla et al 2004;Zinsstag et al 2010). Les fruits et l egumes frais ne sont pas consomm es, ainsi le lait reste pratiquement la seule source de vitamine A, ce qui peut r esulter par des symptômes de carence (Zinsstag et al 2002;Bechir et al 2011Bechir et al , 2012bM€ unch 2012). Un lien direct a puêtre etabli entre le taux de vitamine A dans le sang des femmes et du lait de leur b etail.…”
Section: R Esultats De Rechercheunclassified